Enhancing the Energy Content of Melawan Coal through H2SO4 and NaOH Demineralization - Aliyu Buba Ngulde; Wan Azlina Wan Ab Karim Ghani; Nazmi Mat Nawi; Umer Rashid; Kiman Silas (Indonesian Journal of Chemistry)
The objective of this study was to compare the calorific values, proximate analysis, ultimate analysis, SEM-EDX, XRF, FTIR spectroscopy, and TGA of the control feedstock and coal samples treated with different acid-alkali formulations. We also evaluated the effectiveness of the acid and alkali treatments, individually and in combination, on the structural and chemical properties of Melawan coal. The TGA results indicated that all treated coal samples showed reduced weight loss compared to raw coal, indicating the removal of minerals and volatile components owing to the treatment processes. Based on the DTG curve, the combination treatment (acid followed by base) somewhat stabilizes the coal, leading to a broader and less intense peak. EDS analysis revealed that both H2SO4 and NaOH treatments, individually and in combination, significantly altered the elemental composition of the coal. According to FTIR analysis, the presence of carbonyl groups can affect the performance of coal in processes such as gasification, pyrolysis, or combustion, making it a key functional group of interest for evaluating post-treatment coal properties. The removal of mineral impurities can lead to a higher calorific value, making coal more suitable for energy generation applications.